Predicting drug-induced liver injury from anti-tuberculous medications by early monitoring of liver tests. Issue 2 (February 2021) - Patterson, Benjamin; Abbara, Aula; Collin, Simon; Henderson, Merle; Shehata, Monicka; Gorgui-Naguib, Hannah; Lynn, William; Kon, Onn Min; John, Laurence
Highlights: Routine 2-week liver tests were evaluated in a 1247 patient cohort treated for TB. Anti-tuberculous therapy (ATT) led to drug-induced liver injury (DILI) in 8.3%. Risk of late TB-DILI increased 2.2-fold every 30 U/L rise in pre-treatment ALT. Risk of late TB-DILI increased 2.1-fold every 30 U/L rise in gradient of ALT change. Summery: Objective: Tuberculosis Drug Induced Liver Injury (TB-DILI) is a common and potentially severe complication associated with anti-tuberculous treatment (ATT). Optimal liver test monitoring for standard TB medication has not been established. We describe the predictive value of pre-treatment liver tests (LTs) and at 2-weeks after initiation of ATT for the detection of TB-DILI. Methods: Patients initiating ATT were monitored with routine LTs pre-treatment and after 2-weeks. Logistic regression models were constructed to retrospectively identify pre-treatment variables associated with 'late' TB-DILI (>2 weeks after treatment initiation) and whether pre-treatment and 2-week alanine aminotransferase (ALT) levels could predict late TB-DILI. Results: 1247 patients with active tuberculosis managed at 5 sites across north west London between January 2015 and December 2018 were monitored with routine LTs. 103 cases (8.3%) of ATT-associated DILI were diagnosed. 60 cases (58.3%) of TB-DILI occurred later than 2-weeks. The risk of late TB-DILI was 2.2-fold greater for every 30 U/L increment in ALT pre-treatment (OR 2.16, 95% CI 1.38–3.29 p <0.001) and 2.1-fold greater for every 30 U/L increment in ALT gradient at 2-weeks (OR 2.06, 95% CI 1.52–2.76 p <0.001). Conclusion: Routine 2-week LTs capture early TB-DILI and may be valuable in predicting late TB-DILI in patients on ATT.